The role of personality orientation in predicting quarter life crisis in emerging adulthood: An anchor personality approach - Nur Rohmah Itsnaini; Bagus Riyono (Humanitas: Indonesian Psychological Journal, 2024)
A quarter-life crisis during emerging adulthood is triggered by various worries in the future regarding careers, romantic, and social relationships. This study aims to test the role of anchor personality dimensions in predicting a quarter-life crisis in emerging adulthood. The participants of this study were 279 people in the 18-25 year age group. This study was conducted with the quantitative approach using a survey method through social media. The instruments used were the Quarter Life Crisis Scale and Anchor Personality Inventory. The results of the analysis using the multiple linear regression method showed that anchor virtues have a significant negative relationship in predicting quarter-life crises. However, anchor materials and others show a significant positive relationship in predicting the quarter-life crisis. The implications of this research empirically show the importance of emerging adulthood to be oriented towards virtues to prevent quarter-life crisis and achieve optimal psychological functioning.